The North West London Diabetes Transformation Programme (NWL‐DTP): the journey so far in optimising diabetes care within North West London. (17th April 2019) - Willis, Tony; Chandok, Raj; Delgado, Raquel; Razak, Yasmin; Robertson, Lesley; Dornhorst, Anne; ,
Abstract: In this paper we share learning and outcomes from three years of a North West London Diabetes Transformation Programme (NWL‐DTP) across eight clinical commissioning groups. We have evaluated the improvements in care of 77 382 people with diabetes and 71 562 patients with non‐diabetic hyperglycaemia (NDH) between August 2015 and August 2018, based on primary care data from 229 practices. Significant improvements in care have been achieved through active case finding, primary care improvement programmes and closer multidisciplinary working, supported by a clinical and administrative leadership team. Diabetes prevalence increased by 15% from 67 279 to 77 382 while the NDH register increased from 9071 to 71 562. There was an increase in: patients achieving all nine key care processes by 31.1%; HbA1c ≤58mmol/mol by 6.6%; blood pressure ≤140/80mmHg by 3.8%; cholesterol ≤4mmol/L by 6.8%; all three treatment targets by 4.5%; hypoglycaemia monitoring by 81.1%; collaborative care planning by 74.8%; and NDH annual review by 41.3%. North West London was the largest referrer into the National Diabetes Prevention Programme in the UK over this period. The NWL‐DTP has achieved significant improvements in diabetes care in the context of very high levels of ethnic diversity, significant social deprivation and a complex health commissioning environment. Key enablers supporting the widescale transformation have been clinical leadership, digital systems support, patient engagement and commissioner buy‐in. Further evaluation will focus on health care utilisation, costs and complications in order to understand the impact on key diabetes endpoints. Copyright © 2019 John Wiley & Sons.